2014
DOI: 10.1136/archdischild-2014-307384.125
|View full text |Cite
|
Sign up to set email alerts
|

O-057 Melatonin As A Novel Neuroprotectant In Preterm Infants – A Double Blinded Randomised Controlled Trial (mint Study)

Abstract: have an unfavourable outcome. Cortical, thalamic and WM tissue labels were generated by neonatal atlas-based automated segmentation of the T2-weighted images [1]. Tissue labels were propagated onto the diffusion maps. FA and MD values were determined. Linear regression was performed to assess the correlation between FA/MD and DQ. Estimation of unfavourable outcome with FA/MD in WM and GM was examined using receiver operating characteristic (ROC) analysis. Results Following correction for multiple comparisons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 1 publication
0
6
1
3
Order By: Relevance
“…Из фармакологических нейропротекторов, чья роль в индукции нейропластических процессов может считаться доказанной, у недоношенных детей широко применяется эритропоэтин -причем независимо от режимов и дозировок препарата мультицентровые метааналитические исследования свидетельствуют о более высоком уровне интеллекта в возрасте 18 месяцев у недоношенных при использовании эритропоэтина в первые 48 часов после рождения (оценка когнитивных функций проводилась по шкале Бейли) [40]. В начальной стадии находятся клинические исследования применения с нейропротективной целью у недоношенных мелатонина [41]; в стадии эксперимента -изучение креатина [42], гранулоцитарного колониестимулирующего фактора [43], полусинтетического антибиотика миноциклина [44], эпидермального ростового фактора [45] и диазоксида [46]. Обсуждаются различные инновационные методы возможной доставки нейропротекторов (т.н.…”
Section: оритн и векторы постнатального развития недоношенного младенцаunclassified
“…Из фармакологических нейропротекторов, чья роль в индукции нейропластических процессов может считаться доказанной, у недоношенных детей широко применяется эритропоэтин -причем независимо от режимов и дозировок препарата мультицентровые метааналитические исследования свидетельствуют о более высоком уровне интеллекта в возрасте 18 месяцев у недоношенных при использовании эритропоэтина в первые 48 часов после рождения (оценка когнитивных функций проводилась по шкале Бейли) [40]. В начальной стадии находятся клинические исследования применения с нейропротективной целью у недоношенных мелатонина [41]; в стадии эксперимента -изучение креатина [42], гранулоцитарного колониестимулирующего фактора [43], полусинтетического антибиотика миноциклина [44], эпидермального ростового фактора [45] и диазоксида [46]. Обсуждаются различные инновационные методы возможной доставки нейропротекторов (т.н.…”
Section: оритн и векторы постнатального развития недоношенного младенцаunclassified
“…Було зроблено висновок про те, що нервові центри, відповідні за генерацію біоритмів та гормональний імритинг пінеальнї залози, не спроможні прискорити свій розвиток після передчасних пологів [17]. У 2013 році при проведенні дослідження фармакокінетики мелатоніну у 16 дітей, народжених до 31 тижня гестації, базові рівні його у сироватці визначалися як низькі або не визначалися зовсім [18].…”
Section: вступunclassified
“…протягом 2 годин) було підібрано для досягнення цільової концентрації у сироватці відповідно до рівню мелатоніну у дорослих. Під час проведення магнітно-резонансної томографії білої речовини в еквівалентному скоригованому віці не було виявлено різниці між групами [46]. Однак відсутність позитивного ефекту може бути пояснено порівняно низькою дозою, що вводилася в цьому дослідженні [47].…”
Section: вступunclassified
“…It was found that peak adult melatonin concentration could be achieved by a relatively short (2 h) infusion of low dose (0.1 μg/kg/h) melatonin in preterm infants (Merchant et al, 2013). Using this dosing regime, a Phase 2 RCT (The Mint Study) was conducted to evaluate the neuroprotective effect of melatonin in 58 preterm infants (30 received melatonin and 28 received placebo) (Merchant et al, 2014). No between group difference was shown for the primary outcome, which was a 5% difference in the fractional anisotropy in the white matter measured using MRI at term equivalent age.…”
Section: Emergent Interventionsmentioning
confidence: 99%